N'gine Book Store Enterprise / Irman Shah Idris ... [et al.] - Idris, Irman Shah; Talib, Hazlan; Mohd Hatta, Mohd Farid; Abdul Rashid, Muhammad Rizal; Samsudin, Mohd Sharizal; Tammali, Sabtu Rahman (Faculty of Electrical Engineering, 2003)
The first thing comes out from mind is to run book store and we name it n'gine book store. We chose this because to help students provide their facilities on their subject require as books reference, stationeries, exercise books and etc. These are stage for students to achieve excellent result in their respect exam also contribute to the future